Antimicrobial peptides in hidradenitis suppurativa: a systematic review. (2nd November 2021) - Yao, Y.; Frew, J.W.; Thomsen, S.F.; Ring, H.C.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease of the hair follicle defined by recurrent nodules, tunnels and scarring involving the intertriginous regions. HS is associated with microbial dysbiosis and immune dysregulation. In HS, an increasing number of studies have investigated antimicrobial peptides (AMPs). Objectives: To provide an overview of the literature on AMPs in HS, and to discuss the potential role of AMPs in the pathogenesis of HS. Methods: PubMed, Embase and the Cochrane Library were searched. The titles, abstracts and full texts of all articles were manually screened. Additionally, the reference lists of the included articles were screened and hand searched for relevant studies. Results: The final literature sample comprised 18 retrospective and prospective studies (no reviews or commentaries) published between 2009 and 2020. Conclusions: This review demonstrates the multitude of AMPs in HS. Although the methodology of the studies varied, the included studies indicate a consistent overexpression of human β‐defensin (hBD)‐2, S100A7, S100A8 and S100A9 at both the mRNA and protein levels, and a decreased expression of hBD‐1. Overall, the studies point to a dysregulation of AMPs in both lesional and nonlesional HS skin. Abstract : What is already known about this topic? Various studies have investigated the level of antimicrobial peptides (AMPs) in hidradenitis suppurativa (HS). What does this study add? The data presented in this systematic review point to a dysregulation of AMPs in both lesional and nonlesional skin in HS. Linked Comment:  S.L. Schell and A.M. Nelson. Br J Dermatol 2022; 186:204–205 . Plain language summary available online